1988
DOI: 10.1144/gsl.sp.1988.038.01.18
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Ordovician deformation in the Caledonian-Appalachian orogen

Abstract: Summary Evidence for Ordovician deformation is variably present throughout the Caledonides. The Grampian (late Cambrian-early Ordovician) and Taconian (middle to late Ordovician) major orogenies occurred during this time period and involved plutonism and metamorphism as well as deformation. The Taconian is particularly important in N America, whereas the Grampian (Penebscot), although locally identified, seems less important. Conversely, the Grampian appears to be more important in Scotland and in Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…4) that are intrusive into a sequence of greenschist facies, weakly folded, Ordovician fossil-bearing sedimentary and volcanic rocks. The metamorphism and deformation have been considered to represent a Mid-Ordovician, Taconian equivalent event (Hall and Roberts, 1988). Like the Early Ordovician fossils in the Støren Nappe at Hølonda, the fossils on Smøla also have Laurentian faunal affinities (Bruton and Bockelie, 1979).…”
Section: Keys To U-pb Geochronologymentioning
confidence: 99%
“…4) that are intrusive into a sequence of greenschist facies, weakly folded, Ordovician fossil-bearing sedimentary and volcanic rocks. The metamorphism and deformation have been considered to represent a Mid-Ordovician, Taconian equivalent event (Hall and Roberts, 1988). Like the Early Ordovician fossils in the Støren Nappe at Hølonda, the fossils on Smøla also have Laurentian faunal affinities (Bruton and Bockelie, 1979).…”
Section: Keys To U-pb Geochronologymentioning
confidence: 99%
“…3). Both the Taconic and Famatinian belts have a well-defined structural fabric and corresponding metamorphic zonation (Hall and Roberts, 1988;Dalla Salda et al, 1991), In both the Appalachians and the Famatinian belt, thrust planes affected the lower crust and upper mantle (Haworth et al, 1988;Dalla Salda et al, 1991). The dominant vergence in the Taconic orogen is westward, toward the craton, although easterly vergence at an early stage has been recognized (Hatcher et al, 1989).…”
Section: Famatinian Orogenmentioning
confidence: 99%
“…Another important dating study is that of Dallmeyer et al (1985) and Dallmeyer (1988) who employed the 4°Ar-39Ar method. Plateau ages for hornblendes have revealed a significant Ordovician tectonothermal record in parts of the Khli and Seve Nappes (see also Hall & Roberts 1988 The work of Dallmeyer et al (1985) has shown that, as in northern Norway, the upper allochthon contains imbricated slices of polydeformed rocks carrying an early Caledonian thermal history. Again, this favours a two-stage development of the Scandian orogeny with early ductile thrusting succeeded by later imbrications.…”
Section: Scandinaviamentioning
confidence: 99%
“…The Western Province, in W Spitsbergen,: provides good evidence of middle Ordovician deformation and high-pressure metamorphism (Ohta et al 1983, Hall & Roberts 1988, with the unconformably overlying sedimentary sequence extending up into the Wenlock. While there are no Devonian strata known from this western province, comparison with neighbouring areas has led to the assumption that the second Caledonian tectonothermal event occurred in the period late Wenlock to Pridoli (Harland 1985).…”
Section: Svalbardmentioning
confidence: 99%
See 1 more Smart Citation